2003
DOI: 10.1046/j.1365-3040.2003.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of low molecular weight heat‐shock proteins and total antioxidant activity in the Mediterranean tree Quercus ilex L. in relation to seasonal and diurnal changes in physiological parameters

Abstract: The total antioxidant activity (TAA) and the accumulation of small heat shock proteins (sHsps) were analysed under field conditions in Quercus ilex with regard to organ ontogeny and the physiological state of the plant. The results point toward the participation of sHsps and an increase of TAA in the general adaptation syndrome (GAS) of woody Mediterranean evergreens. In leaves and stems, there was a definite TAA seasonal pattern but no effect from diurnal variations or from the current stage of organ ontogeny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Our data showed primary metabolic adjustments to (1) maintain photosynthetic carbon uptake at mild drought stress, and (2) to protect leaves from oxidative damage at more severe levels of drought stress. Additional adjustments involving the production of small heat shock proteins (Verdaguer et al ), peroxidases (Echevarría‐Zomeño et al ) and terpenes (Peñuelas and Llusià , Blanch et al ) have been observed in Q. ilex leaves under high temperatures and low water availability. These adjustments also act against oxidative stress by increasing thermotolerance, ROS scavenging or cell repairing.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed primary metabolic adjustments to (1) maintain photosynthetic carbon uptake at mild drought stress, and (2) to protect leaves from oxidative damage at more severe levels of drought stress. Additional adjustments involving the production of small heat shock proteins (Verdaguer et al ), peroxidases (Echevarría‐Zomeño et al ) and terpenes (Peñuelas and Llusià , Blanch et al ) have been observed in Q. ilex leaves under high temperatures and low water availability. These adjustments also act against oxidative stress by increasing thermotolerance, ROS scavenging or cell repairing.…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms account for the photoprotective defence in the winter in Q. ilex, increased activity of total hydrophilic antioxidants (Verdaguer et al 2003), increased ascorbate content (García-Plazaola et al 1999), and increases in the polyamine, putrescine (Pintó-Marijuan et al 2006. The flavonol-hexosides detected in highest amount in this season might also contribute to photoprotection (Winkel-Shirley 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression of some sHSPs has been detected in all plant tissues under different conditions (Almoguera et al 1993;Coca et al 1996;Sun et al 2001;Verdaguer et al 2003;Swindell 2006;Swindell et al 2007;Qin et al 2008;Siddique et al 2008;Waters et al 2008;Sarkar et al 2009;Weston et al 2011;Haq et al 2013;Merino et al 2014;Park et al 2015). In rice, the Oshsp26 gene was induced by heat stress: the transcript level was the highest when rice leaves were treated at 42°C for 2 h. It was also found that Oshsp26 gene was expressed following oxidative stress even in the absence of heat stress (Lee et al 2000).…”
Section: Introductionmentioning
confidence: 99%